Non-destructive test and evaluation of materials - Prasad, J.; Nair, C. G. Krishnadas (Tata McGraw-Hill, 2011)
Non-Destructive Test and Evaluation of Materials offers every engineer, technical professional, teacher and student engaged in NDE activities, an authoritative guide to the most commonly used and emerging methods of NDE. It comprehensively prepares its readers for professional NDE Level I, II and III tests. The book elaborately provides guidelines on developing specific NDE techniques and criteria for acceptance of materials for various applications as well as NDE requirements of design, manufacturing and maintenance agencies. Containing over 200 illustrations, this essential reference discusses: Complete overview of NDE technology and its capabilities, Principles and applications of different NDE methods, Industrial applications of NDE, Modern trends in various disciplines of NDE.